2007
DOI: 10.1074/jbc.m705392200
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity and Processivity of Reverse Transcription by the Human Mitochondrial DNA Polymerase

Abstract: We have characterized, by transient-state kinetic methods, the polymerase and exonuclease activities of the human mitochondrial DNA polymerase (pol ␥) during reverse transcription, employing a synthetic oligonucleotide consisting of a DNA primer and an RNA template. In comparison with the kinetic parameters observed with a DNA template, the rate of correct deoxynucleotide incorporation was reduced 25-fold (5.5 ؎ 0.2 s ؊1 ), whereas the dissociation constant (K d ) for nucleotide binding was increased 4-fold (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Studies investigating the physiological consequence of reverse transcriptase activity by human pol γ opposite a single ribonucleotide found that pol γ stalls after incorporating a single deoxyribonucleotide [57]. In addition, recent results reveal that the efficiency of bypassing a single ribonucleotide in the template DNA was 51% compared to a control template containing no ribonucleotides [40].…”
Section: Human Mitochondrial Dna Polymerase Catalytic Subunit Andmentioning
confidence: 99%
“…Studies investigating the physiological consequence of reverse transcriptase activity by human pol γ opposite a single ribonucleotide found that pol γ stalls after incorporating a single deoxyribonucleotide [57]. In addition, recent results reveal that the efficiency of bypassing a single ribonucleotide in the template DNA was 51% compared to a control template containing no ribonucleotides [40].…”
Section: Human Mitochondrial Dna Polymerase Catalytic Subunit Andmentioning
confidence: 99%
“…Because it was previously shown that the affinity of the human DNA pol ␥ with RNA/DNA substrates is similar to that with DNA/DNA substrates, comparison of steady state kinetic parameters becomes valid (22,23). Reaction mixtures (10 l) contained 25 mM HEPES-KOH (pH 7.6), 2 mM 2-mercaptoethanol, 0.1 mM EDTA, 5 mM MgCl 2 , 50 nM radiolabeled substrate, 10 nM exonuclease-deficient WT or E895A Shown is a molecular model of the human DNA pol ␥ active site with incoming ddCTP (dark blue), and Mg 2ϩ (gray spheres).…”
Section: Methodsmentioning
confidence: 99%
“…Previous biochemical studies using purified DNA polymerase ␥ suggested that the enzyme is an efficient reverse transcriptase and possesses the ability to incorporate and extend ribonucleotides (22,23). However, a comprehensive analysis of incorporation, discrimination, extension, and bypass of ribonucleotides by DNA pol ␥ is still lacking.…”
mentioning
confidence: 99%
“…Furthermore, Pol γ can perform exonuclease cleavage of mismatched dNMPs opposite a RNA template [50]. The reverse transcriptase activity of Pol γ was later found to be not processive, incorporating one dNTP and dissociating from the primer/template [51]. This indicates that the physiological significance of this phenomenon may be linked to single ribonucelotides present throughout the template strand.…”
Section: Kinetic Characterization and Analysis Of Human Mitochondrmentioning
confidence: 99%
“…This indicates that the physiological significance of this phenomenon may be linked to single ribonucelotides present throughout the template strand. The weaker interaction between Pol γ and DNA/RNA primer-templates also serves to explain the increased steady-state rate of incorporation versus DNA/DNA primer-templates, as the steady-state rate is governed by the rate of primer-template release [51]. …”
Section: Kinetic Characterization and Analysis Of Human Mitochondrmentioning
confidence: 99%